THE IMPACT OF EXCHANGE RATE FLUCTUATIONS ON CAPITAL ADEQUACY IN LIGHT OF THE CORONA PANDEMIC: AN ANALYTICAL STUDY ON A SAMPLE OF IRAQI COMMERCIAL BANKS FOR THE PERIOD (2011-2021) - Murtaza Hadi; Nawar Makttoof; Mohammed S. Ahmed (Scholar Express Journals, 2022)
The study aims to find out the effect of the exchange rate on the capital adequacy index with the introduction of the impact of the pandemic as a modified intermediate variable, due to the exposure of all sectors and their activities to major problems as a result of the exchange rate change at the end of 2020 and the exposure of the world and Iraq in particular to the Corona pandemic at the beginning of 2020, forcing and others from Countries to stop life as a global precaution. The variable represented by the exchange rate (market rate) and the Corona pandemic (as a modified intermediate variable) and the approved variable represented by the capital adequacy index, and certain software such as EViews 12 and Excel were used for the time period 2011-2021 and for four banks listed on the Iraq Stock Exchange. . After a series of calculations at the level of financial, statistical and standard analysis, the researcher concluded that the pandemic significantly affected the dependent variable and strengthened the results of the impact of exchange rate fluctuations on the banking capital adequacy index. Taking into account in formulating the policies of the financing and investment banks in order not to expose these banks to exchange rate risks and the risks associated with them as a result, and to ensure that they maintain their competitive and market position, in addition to that interest in studying the problems of the times and epidemics that appear from time to time and matters related to the environment because they are problems that may be a result Human intervention in it and its consequences are great on all activities, including banking
Keywords: exchange rate; capital adequacy index; corona pandemic